2011
DOI: 10.1016/j.ecss.2011.05.026
|View full text |Cite
|
Sign up to set email alerts
|

In situ flume measurements of resuspension in the North Sea

Abstract: Any queries or remarks that have arisen during the processing of your manuscript are listed below and highlighted by flags in the proof. Location in article Query / Remark: Click on the Q link to find the query's location in text Please insert your reply or correction at the corresponding line in the proof Q1 Please check the affiliations. Q2 As per the journal stylesheet, Highlights with 3e5 bullet points (not more than 120 characters per point including spaces) is mandatory. Hence kindly check and provide th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…Because of a relatively small water depth and a large water surface area, shallow lakes are particularly susceptible to eutrophication-induced algal bloom and water quality degradation [8][9][10]. For a shallow lake, the wind-induced shear stress on the lake surface can be efficiently transferred downward through the shallow water column to the lakebed, resuspending bed sediments from which nutrients can be released into the ambient water [11][12][13][14][15][16]. The threshold shear stress, beyond which the resuspension of bed sediments will incept, depends on the physiochemical characteristics (e.g., texture, age and compaction) of the sediments [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Because of a relatively small water depth and a large water surface area, shallow lakes are particularly susceptible to eutrophication-induced algal bloom and water quality degradation [8][9][10]. For a shallow lake, the wind-induced shear stress on the lake surface can be efficiently transferred downward through the shallow water column to the lakebed, resuspending bed sediments from which nutrients can be released into the ambient water [11][12][13][14][15][16]. The threshold shear stress, beyond which the resuspension of bed sediments will incept, depends on the physiochemical characteristics (e.g., texture, age and compaction) of the sediments [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…45 In situ measurements have shown that SPM can vary by a factor of 2 or more during the day due to horizontal advection and/or vertical resuspension forced by tides or wind events. 46,47 Temporal frequency afforded by GOCI for the first time allows us to study these high temporal frequency variations in the water surface.…”
Section: Physical and Bio-optical Conditions During Geostationary Ocementioning
confidence: 99%
“…Tolhurst et al, 2006;Lundkvist et al, 2007b). While coarse non-cohesive sediments show predictable relationships between grain size and erosion threshold (Dyer, 1986;Thompson et al, 2011), the erosion dynamics of cohesive sediments is more complex and difficult to predict alone from physical properties, such as particle size, water content, bulk density, organic content, depositional history and air exposure. The erosion threshold of cohesive coastal sediments is instead under control of biological factors including microphytobenthos activity, macrophyte growth as well as meio-and macrofauna activity Paterson et al, 2000;De Brouwer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%